Pendampingan Belajar Berhitung Dengan Menggunakan Model Pembelajaran Kooperatif Tipe Number Head Together di Desa Sungai Buluh - Mayada, Mayada; Fitriah, Fitriah; Nuragustina, Waviq; Milla, Milla; Nurmeidina, Rahmatya (Institut Teknologi Pendidikan Indonesia, 2024)
This community service is carried out to help schools in villages that are not facilitated in learning so that they can improve the abilities of students in villages and schools. Schools in this village are schools that are quite difficult to reach by the wider community because access is quite limited. In addition, the level of attendance of students who are not too high is also a problem in terms of learning. Based on the results of interviews with teachers who teach mathematics at SDN 3 Sungai Buluh that students who study are more emphasized on basic abilities such as reading, writing and arithmetic to support their abilities later. The purpose of this community service is to provide assistance in learning mathematics. The aim is to improve students' ability to count. The method used in this service is descriptive qualitative with assistance to a target group. Learning assistance is carried out directly to students at SDN 3 Sungai Buluh using the Number Head Together cooperative model with arithmetic materials such as addition, subtraction, and multiplication. The results of the final test of the numeracy learning assistance showed that the results of students' numeracy skills increased compared to before. Students are very enthusiastic about participating in tutoring as shown by students asking for additional questions to work on. Students' motivation to learn mathematics also increased, students stated that counting in mathematics was fun.